Clinical profile and outcomes of Non-Hodgkin's lymphoma in children: A report from a tertiary care hospital from India - Jagdish Prasad Meena; Aditya Kumar Gupta; Mansingh Parihar; Rachna Seth (Indian Journal of Medical and Paediatric Oncology)
Background: Non-Hodgkin's lymphoma (NHL) is an aggressive malignancy. Its outcome has improved over the past decades. Although it accounts for 8%–10% of all childhood cancers, very less information about its clinical presentation and outcomes is available from India. Our objective was to study the clinical presentation and outcomes in children (<15 years) with NHL at our center. Methodology: We retrospectively analyzed 26 children diagnosed with NHL at our center from August 2008 to June 2014 and followed them up to May 2017. Results: The median age at the time of diagnosis was 7.7 years (2.5–13 years). Abdominal distension and an abdominal lump were the most common presenting features occurring in 75%, followed by fever (73.8%) and weight loss (46.2%). Most patients had advanced-stage (Stage III/IV, 92.3%) disease at presentation. The primary presentation was extranodal in 57.7%, nodal in 26.9%, and combined in 15.4%. Burkitt's lymphoma (BL) was the most common subtype (46.2%), followed by T-lymphoblastic lymphoma, diffuse large B-cell lymphoma, and anaplastic large-cell lymphoma. Three patients did not take treatment. The median follow-up of patients was 48 months (36–99 months). Nineteen patients achieved remission and four had progressive disease. Significantly better event-free survival (EFS) was found with younger age and lower stage of presentation. The EFS did not significantly differ with sex, group of disease, lactate dehydrogenase levels, and presenting features. Conclusions: Our cohort of patients with NHL showed characteristics similar to those reported from other developing countries. NHL occurred at a younger age, with a higher incidence of BL. The outcome for patients aged >10 years was poor. The outcome of NHL was comparable to that of other centers in the world.